Instruction for the authors: Instrucción para los autores - Editorial, Comite (2018)
GENERAL RULESGENERAL RULES The Journal of the Faculty of Human Medicine of the Ricardo Palma University (http://revistas.urp.edu.pe/index.php/RFMH) is aquarterly scientific journal, which publishes original articles in Spanish and English, and will consider for publicationthose works related to public health, surgery, clinical sciences and basic sciences, said works must not have beenpreviously published, nor sent simultaneously to other scientific journals. The magazine of the Faculty of Human Medicine (RFMH) of the Ricardo Palma University adheres to the recommendations of theInternational Committee of Medical Journal Editors (http://www.icmje.org).